1993
DOI: 10.1111/j.1365-2818.1993.tb03286.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure‐property relationships in silicate‐matrix composites

Abstract: SUMMARY Electron microscopy and associated analytical spectroscopic techniques have been used to characterize interfaces in SiC‐fibre/silicate‐matrix composites. Interface structure, formed via reaction during hot‐press fabrication, is a function of time, temperature, matrix composition and fibre type. Interfaces with Nicalon or Tyranno fibres vary from amorphous carbon in fine precipitated form to continuous graphitic layers. Interface behaviour in a stressed composite, and hence the matrix microcracking stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 17 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…However, a transition layer is also observed in SiC f -YMAS composites. A similar transition layer has also been found in SiC f -LAS Ponthieu et al, 1994) and in SiC f -Duran composites (Lewis et al, 1993;Hähnel et al, 1994). The present study has shown that the transition layer is a diffusion zone for matrix elements except yttrium in SiC f -YMAS composites.…”
Section: Edx Analyses Of Interfacial Regionsupporting
confidence: 90%
“…However, a transition layer is also observed in SiC f -YMAS composites. A similar transition layer has also been found in SiC f -LAS Ponthieu et al, 1994) and in SiC f -Duran composites (Lewis et al, 1993;Hähnel et al, 1994). The present study has shown that the transition layer is a diffusion zone for matrix elements except yttrium in SiC f -YMAS composites.…”
Section: Edx Analyses Of Interfacial Regionsupporting
confidence: 90%
“…The aim of the present work is to assess the effects of post-fabrication ageing heat-treatments upon the microstructure and mechanical properties of a BMAS glass-ceramic matrix composite. A novel indentation system Lewis et al, 1993) has been used to assess interfacial micromechanics parameters (2l7 and T) of the BMAS composite in both the as-fabricated and the aged conditions. Data obtained with this technique have subsequently been related to macro-mechanical behaviour and interface microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…8-10. These figures show a dependency of dynamic toughness and impact energy for unidirectional 0 and 90 fiber orientation Al 2 O 3 -borosilicate composites up to 950 C, where the Al 2 O 3 -96% silica composite showed little or no dependency on increasing test temperatures, before dropping off at temperatures higher than 750 C. It is possible that the combination of matrix microcracks and oxidizing atmosphere had some embrittling effect on the Al 2 O 3 fiber reinforced 96% silica composite at elevated temperature, and that as temperature increases the thermal mismatch between fiber-matrix decreases leading to an increase in fiber-matrix interfacial bonding and thus increasing tendency to embrittlement, [9,21,[25][26][27][28], as shown in Figs. 11(a) and (b).…”
Section: Theoretical Backgroundmentioning
confidence: 94%
“…Further tests were conducted in inert environments, [21,28], implied that exposure to high temperature air was responsible for the degradation because under these non-air environments no loss of strength or toughness and fibrosity occurred. This indicates that oxygen in air probably is the active specie involved in the loss of both flexure strength and toughness of such composites.…”
Section: Theoretical Backgroundmentioning
confidence: 99%